Household incomes in New Zealand: The impact of the market, taxes and government spending, 1987/88–1997/98 - Ron Crawford; Grant Johnston (New Zealand Government, The Treasury, 2004)
How well have New Zealand households fared over a decade of extensive economic and social changes? This study compares household incomes in 1997/98 with household incomes in 1987/88, using the concept of "final income". Final income is a measure of the income accruing to households after adjusting for payments to, and benefits from, central government, whether these benefits are in cash or in kind. In particular, receipt of government health and education services is counted as adding to a household's income, and payment of consumption taxes is counted as taking away from a household's income. In all income deciles, the real final incomes of households were, on average, at least the same in 1997/98 as they were in 1987/88, and in most cases had increased. Government intervention, through taxes, cash benefits and social services, has maintained the incomes of less well-off households over a period of upheaval in New Zealand.
Keywords: D1; D31; H5; H22; I0; J1; 330; final income; income distribution; redistribution; fiscal incidence; income inequality; New Zealand